Venomics of the Enigmatic Andaman Cobra (Naja sagittifera) and the Preclinical Failure of Indian Antivenoms in Andaman and Nicobar Islands - Attarde, Saurabh; Khochare, Suyog; Iyer, Ashwin; Dam, Paulomi; Martin, Gerard; Sunagar, Kartik (Frontiers in Pharmacology, 2021)
The Andaman and Nicobar Islands are an abode to a diversity of flora and fauna, including the many endemic species of snakes, such as the elusive Andaman cobra (Naja sagittifera). However, the ecology and evolution of venomous snakes inhabiting these islands have remained entirely uninvestigated. This study aims to bridge this knowledge gap by investigating the evolutionary history of N. sagittifera and its venom proteomic, biochemical and toxicity profile. Phylogenetic reconstructions confirmed the close relationship between N. sagittifera and the Southeast Asian monocellate cobra (N. kaouthia). Overlooking this evolutionary history, a polyvalent antivenom manufactured using the venom of the spectacled cobra (N. naja) from mainland India is used for treating N. sagittifera envenomations. Comparative evaluation of venoms of these congeners revealed significant differences in their composition, functions and potencies. Given the close phylogenetic relatedness between N. sagittifera and N. kaouthia, we further assessed the cross-neutralising efficacy of Thai monovalent N. kaouthia antivenom against N. sagittifera venoms. Our findings revealed the inadequate preclinical performance of the Indian polyvalent and Thai monovalent antivenoms in neutralising N. sagittifera venoms. Moreover, the poor efficacy of the polyvalent antivenom against N. naja venom from southern India further revealed the critical need to manufacture region-specific Indian antivenoms.